Lithofacial models of productive deposits of the Moshakov formation within the southwesten part of the Siberian platform - O. A. Antipova; O. V. Postnikova; V. S. Yakushev; L. V. Miloserdova (Известия высших учебных заведений: Геология и разведка)
The oil and gas potential of the south-western part of the Siberian platform is related mainly to the Vendian reservoir rocks. One of the most prospective objects are the deposits of Taseeva series, which include clastic deposits of the Moshakov formation. These deposits are widely developed along the periphery of the Baykit anteclise and adjacent territories. Gas deposits were discovered at the Abakan, Imbinskoe and Ilbokichskoye fields in deposits of Taseeva group. The Vendian terrigenous deposits of the Moshakov formation within the Angara folded zone formed in the environment of different zones of the tidal plain. The deposits have a cyclical structure with a regressive orientation of the sedimentary cyclites in the lower part and a regressive-transgressive one in the upper part. The lower parts of the regressive cyclites are represented by silty clay rocks, which are replaced up in the section by more coarse grained ones. The upper parts of the cyclite are built mostly by the sandy variations. Numerous traces of burrowing organisms have been identified in the rocks, in particular, large forms of Skolithos. Regressive-transgressive cychtes have a slightly different structure. Silty argillites occur in the lower part of the cyclite, which are replaced upwards along the section by mixed sulphate-carbonate-clay rocks. In the middle part of the cychte there are thin sandy interbeds. The reservoir rocks are represented by coarse, medium and differently grained sandstones. The clastic part of sandstones is composed of quartz, feldspars and Augments of volcanic and metamorphic rocks. Void space refers to the intergranular type and is also associated with leaching voids in the zones of dissolution of carbonate cement and feldspars. The reservoir rocks are confined to the upper parts of the regressive and middle parts of the regressive-transgressive cychtes formed in the conditions of the sandy covers of the tidal plain. Reservoir properties of rocks are determined not only by their facies but also to a large extent by the intensity and direction of secondary transformations including fracturing.